(untitled) (Research, Society and Development, 2025)
Objective: To investigate the motivations associated with psychotropic medication use among medical students. Methods: An integrative review was conducted using PubMed and the Virtual Health Library (VHL), applying the descriptors students, medical AND psychotropic drugs. Original articles published in the last ten years and freely available in full text were included. The search yielded 122 publications—82 from PubMed and 40 from the VHL. After title and abstract screening, 45 studies were selected, and 12 met all eligibility criteria following full-text reading. Results: Motivations for psychotropic use were grouped into two main categories: medical prescription and self-medication. Medical indications included attention-deficit/hyperactivity disorder, insomnia, anxiety, and depression, with the latter two more prevalent among women and senior medical students. Regarding self-medication, stress relief, academic overload and attempts to enhance cognitive performance were the most frequently cited reasons. Medical students exhibited higher rates of self-medication compared to students in other health fields, particularly those working while studying or living away from their families. The most commonly used pharmacological classes were antidepressants, benzodiazepines, and hypnotics, with fluoxetine, zolpidem, trazodone, and sertraline being the most frequently reported medications. Most students indicated receiving regular follow-up from general practitioners or psychiatrists. Conclusion: Psychotropic medication use among medical students is primarily driven by psychiatric symptoms, stress management, and efforts to improve academic performance.